DEVELOPMENT OF BUSINESS STRATEGIES USING SWOT ANALYSIS IN PALASARI COFFEE BANDUNG - Yosep Hernawan; Musafa .; Srie Wijaya Kesuma Dewi (Jurnal Ilmiah Manajemen "E M O R", 2019)
In 2016, West Java was awarded as best coffe in the world at the Expo Coffee event. One of regions thar represented Jawa Barat is palasari coffee, Kampung Legok Nyenang, Desa Girimekar, Kabupaten Bandung. This potenstial is expected to increase and improve their quality of life of its citizen. It would require a draft development strategy in order to optimize the potential of palasari coffee. This research will accommodate the needs of the design and development of business strategies palasari coffee. Retrieval of data was taken from palasari coffee using interview and observation methods. The collected data is processed and analyzed using analysis tool  SWOT,  IFAS & EFAS tables and SWOT matriks. The conclusion is that the position of the palasari coffee is at a favorable stage. The result  has a score of strength greater than weakness score, and an opportunity score greater than the threat score. It is in quadrant 1 (growth). The implementation of the appropriate  strategy is expected palasari coffee can continue to grow and develop as one of the potential assets of the region.